Pengaruh Kehadiran dan Tunjangan Profesi Guru Terhadap Prestasi Kerja Di MIN 1 Kota Cilegon (Studi Kasus MIN 1 Kota Cilegon) - Islahudin Islahudin (Sejahtera: Jurnal Inspirasi Mengabdi Untuk Negeri, 2023)
This study aims to determine the effect of teacher's professional attendance and benefits on work performance in MIN 1 Cilegon City. The independent variable in this study is the attendance and professional allowance of the teacher while the dependent variable is work performance. The research used in this study uses an associative method with a quantitative approach. The population in this study was the MIN 1 Cilegon Teacher with a total of 30 Educators. Sampling 30 respondents of saturated samples. Data were collected by questionnaire and analyzed by SPSS version 26. The statistical methods used were normality test, classic assumption test of linearity test, simple correlation test, regression test and coefficient of determination analysis. Based on the results of the study "The Effect of Teacher Professional Attendance and Allowance on Job Performance in MIN 1 Cilegon City", can be seen as follows: The results of the product moment correlation coefficient analysis show that r = 0.574 means that it has a moderate or significant correlation between attendance and allowance variables on work performance. In the calculation of the hypothesis obtained results tcount> t table (6.006> 2.001) Based on the calculations in the simultaneous F test obtained Fcount = 6.822, while the value of F table = (dk = nk-1 = 30-2-1 = 27 amounted to 3.35 with a real level of 0.05 Fcount> F table (6.822> 3.35) thus Ho3 is rejected and Ha3 is accepted with a significance level of (0.004 <0.05), it can be concluded that "there is a simultaneous and significant relationship between presence (X) and teacher professional allowance (X2) for work performance (Y) in MIN I Cilegon City ".